2021
DOI: 10.1016/j.hlc.2021.02.004
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Manifestations in COVID-19: A Review

Abstract: COVID-19 has rapidly spread around the world and threatened global health. Although this disease mainly affects the respiratory system, there is increasing evidence that SARS-CoV-2 also has effects on the cardiovascular system. Echocardiography is a valuable tool in the assessment of cardiovascular disease. It is cost-effective, widely available and provides information that can influence management. Given the risk of personnel infection and equipment contamination during echocardiography, leading world societ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(48 citation statements)
references
References 62 publications
4
43
0
Order By: Relevance
“…A recent study regarding echocardiographic findings among COVID patients reported that half of them presented a significant tricuspid regurgitation followed by aortic regurgitation and mitral regurgitation 47 . Tricuspid regurgitation is the most common VHD reported in COVID-19 patients and its severity could directly reflect the impairment of the pulmonary circulation during the infection resulting in pulmonary hypertension, especially in patients with severe pneumonia and respiratory insufficiency 48 .…”
Section: Cardiac Valves and Pericardiummentioning
confidence: 99%
“…A recent study regarding echocardiographic findings among COVID patients reported that half of them presented a significant tricuspid regurgitation followed by aortic regurgitation and mitral regurgitation 47 . Tricuspid regurgitation is the most common VHD reported in COVID-19 patients and its severity could directly reflect the impairment of the pulmonary circulation during the infection resulting in pulmonary hypertension, especially in patients with severe pneumonia and respiratory insufficiency 48 .…”
Section: Cardiac Valves and Pericardiummentioning
confidence: 99%
“…2021 has seen further articles about COVID-19 but rather than initial, well-considered pandemic guidance offered by experts and projections and predictions of likely effects to come, we are now seeing original contributions and commentary about the lived experience from the “fields of battle” in Australia and elsewhere in terms of: the acute disease, its manifestations and complications [ [33] , [34] , [35] , [36] , [37] , [38] ]; the adaptations to and opportunities in COVID-19 care [ 39 , 40 ] and in other care settings [ 41 ]; the effects of the COVID-19 pandemic on diagnostic cardiac procedural volumes [ 42 , 43 ] and cardiac surgery [ 44 , 45 ]; and, more recently, the reported side-effects of COVID-19 vaccination [ 46 , 47 ].…”
Section: : More About Covid-19mentioning
confidence: 99%
“…Among the findings reported or reviewed: the echocardiographic manifestations of COVID-19 are many [ 34 ]; troponin elevation was common but clinical sequelae were uncommon in patients with COVID-19 requiring hospitalisation in Australia [ 36 ]; and, atrial fibrillation was determined to be a predictor of mortality in high risk COVID-19 patients [ 37 ].…”
Section: : More About Covid-19mentioning
confidence: 99%
“…The impact of the global health crisis due to the virus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2)—the causative pathogen of the coronavirus disease 2019 (COVID-19)—has begun to alter with the timely development, approval and administration of vaccines [ 1 ]. Although SARS-CoV-2 infection primarily targets the respiratory system [ [2] , [3] , [4] , [5] , [6] ], it is now recognised that the infection and its clinical manifestations are systemic [ [7] , [8] , [9] , [10] , [11] , [12] ], and also affecting the cardiovascular system of adults and children [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Cardiac complications of variable severity with acute and long-term sequelae are now known to include acute myocardial injury, arrhythmias, vasculitis and endothelial dysfunction, thrombosis, myocardial fibrosis, and myocarditis [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ].…”
mentioning
confidence: 99%
“…Although SARS-CoV-2 infection primarily targets the respiratory system [ [2] , [3] , [4] , [5] , [6] ], it is now recognised that the infection and its clinical manifestations are systemic [ [7] , [8] , [9] , [10] , [11] , [12] ], and also affecting the cardiovascular system of adults and children [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] ]. Cardiac complications of variable severity with acute and long-term sequelae are now known to include acute myocardial injury, arrhythmias, vasculitis and endothelial dysfunction, thrombosis, myocardial fibrosis, and myocarditis [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. The cardiovascular and cellular pathophysiology of COVID-19, and the clinical management of previously healthy subjects and patients with existing cardiovascular or other disease conditions remain under intense investigation particularly as early in the pandemic, myocarditis was identified as a risk factor for increased mortality in COVID-19 patients [ [23] , [24] , [25] ].…”
mentioning
confidence: 99%